2020
DOI: 10.32479/ijeep.8418
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Gross Domestic Product and Energy: A Critical Comment

Abstract: Since 1978, an important literature has been developed on the relationship between gross national product and energy. The obvious interest in this relationship is a result of the global interest in reducing the use of energy without impairment of economic growth. Most studies do not have an economic model underlying the statistical models. In the absence of an economic model supporting the estimable equations, the statistical results can be interpreted arbitrarily or they may not have an interpretation that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Magazzino (2017) found that renewable energy consumption increases due to improvements in the GDP level. Magazzino (2016) concluded that a feedback and growth hypothesis exists between CO 2 emissions and GDP in Armenia, Georgia, and Azerbaijan, while a neutrality hypothesis exists in Turkey. While trade openness increases environmental pollution, the EKC hypothesis is invalid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Magazzino (2017) found that renewable energy consumption increases due to improvements in the GDP level. Magazzino (2016) concluded that a feedback and growth hypothesis exists between CO 2 emissions and GDP in Armenia, Georgia, and Azerbaijan, while a neutrality hypothesis exists in Turkey. While trade openness increases environmental pollution, the EKC hypothesis is invalid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nonetheless, studies associated with pollution control or abatement are also there in the prevailing literature (Magazzino, 2016(Magazzino, , 2017Magazzino et al, 2023). In such a context, this section briefly outlines a few related studies in this area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role of energy consumption on economic growth is well fertile in literature (Magazzino, 2016(Magazzino, , 2017. However, for the last couple of decades, the environment and energy literature debates have revolved around the pollution that emanates from energy use and its abatement mechanism (Ssali et al, 2019).…”
Section: Energy Consumption and Environmental Degradationmentioning
confidence: 99%
See 2 more Smart Citations